Performance of Banking Industry In India - a Study: Exploring the challenges, opportunities, and strategies in the Indian banking industry (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The banking industry in India has a huge canvas ofhistory, which covers the traditional banking practices from the time ofBritishers to the reforms period, nationalization to privatization of banks andnow increasing numbers of foreign banks in India. Therefore, Banking in Indiahas been through a long journey. Banking industry in India has also achieved anew height with the changing times. The use of technology has brought arevolution in the working style of the banks. Nevertheless, the fundamentalaspects of banking i.e. trust and the confidence of the people on theinstitution remain the same. The majority of the banks are still successful inkeeping with the confidence of the shareholders as well as other stakeholders.However, with the changing dynamics of banking business brings new kind of riskexposure. In this paper an attempt has been made to identify the generalsentiments, challenges and opportunities for the Indian Banking Industry. Thisarticle is divided in three parts. First part includes the introduction andgeneral scenario of Indian banking industry. The second part discusses thevarious challenges and opportunities faced by Indian banking industry. Thirdpart concludes that urgent emphasis is required on the Indian banking productand marketing strategies in order to get sustainable competitive edge over theintense competition from national and global banks. This article is a small seed to existing branch ofknowledge in banking industry and is useful for bankers, strategist, policymakers and researchers.